Determining the rational technological processing modes for achieving optimal operational characteristics of the surface layer obtained by electric spark alloying using carbide electrodes - Prunko, Ihor; Voitsekhivska, Tetyana; Dem’yanchuk, Yaroslav (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the wear resistance of surfaces after electric spark alloying in contact with elastically fixed abrasive grains. The task addressed relates to the lack of technological modes for electric spark processing, in particular for hard alloys T15K6 and VK8. A rational mode has been determined, under which samples with an optimal surface profile, a uniform structure, and minimal internal defects were obtained. The choice of the technique for machining high-wear surfaces by the electric spark alloying method is due to its simplicity and accessibility. Waste can be used as electrodes, specifically hard alloy plates of a cutting tool that have failed. At the same time, there are a number of unresolved issues related to the choice of optimal machining modes that would ensure high wear resistance of the machined surfaces. A technique for testing machined parts for wear has been proposed. It was found that the highest predicted wear resistance would be demonstrated by parts processed by the electric spark alloying (ESA) method using the VK8 electrode, with the capacitor bank capacity of 330 ± 30 μF and the electrode vibration frequency of 125 ± 25 Hz. They combine high surface microhardness (13.5 MPa) and residual compressive stresses in the deposited layer (–90 MPa). The results are attributed to the physical and mechanical processes occurring in the metal during electric spark alloying. These conditions were created by different values of technological parameters. A feature of the results is that it was established that not only the hardness of the deposited layer but also the magnitude of internal stresses in this layer have a significant impact on the operational parameters. Practical application implies that electric spark alloying could become an alternative technology for strengthening the surfaces of parts that work in contact with abrasives (mechanical engineering, medicine)